Modulation of adipose inflammation and mitochondrial pathways by a yeast-derived β-1,3/1,6-glucan and vitamin complex: an open-label pilot study of Lalmin® immune pro in older overweight adults - Pritchard, Jack; Struszczak, Lauren; Henry, Cealan; Lugtmeijer, Celeste; Bowtell, Joanna; O’Leary, Mary (Frontiers in Nutrition, 2025)
Chronic low-grade inflammation and mitochondrial dysfunction contribute to age- and obesity-related disease, yet few nutritional interventions have been shown to impact both processes. This open-label pilot study evaluated the effects of a 28-day supplementation with Lalmin® Immune Pro—delivering a daily dose of 250 mg yeast-derived β-1,3/1,6-glucan, 13.7 mg zinc, 65.0 μg selenium, and 500 IU vitamin D₂—in older, overweight adults. Proteomic profiling of subcutaneous adipose tissue was performed using tandem mass tag quantitative proteomics, with pathway-level analysis via Reactome’s CAMERA workflow. 3,172 proteins were consistently detected across all samples and used for pathway analysis. A total of 107 pathways were significantly modulated post-supplementation, including downregulation of innate (FDR = 9.3 × 10−7; Log2FC = −0.060) and adaptive immune pathways (FDR = 0.025; Log2FC = −0.020). Conversely, mitochondrial pathways were upregulated, including cristae formation (FDR = 6.3 × 10−5; Log2FC = 0.304), protein import (FDR = 1.0 × 10−5; Log2FC = 0.273), and respiratory electron transport (FDR = 1.4 × 10−5; Log2FC = 0.210). Cytokine assays of adipose explant conditioned media revealed significant reductions in the secretion of leptin (−71%), MCP-1 (−50%), IL-8 (−59%), IL-6 (−38%), and MIP-3α (−37%) post-supplementation. These findings suggest that components of Lalmin Immune Pro may exert dual immunometabolic effects, dampening inflammatory signalling while enhancing mitochondrial function in adipose tissue. Randomised controlled trials of both Lalmin® Immune Pro and yeast-derived β-1,3/1,6-glucan alone is warranted to confirm these preliminary findings and evaluate their relevance to metabolic health.